دراسة إمكانية استخدام برامج تكاليف الجودة في الشركات الصناعية السورية - زيود, لطيف; أسعد, باسل; ياسين, أيام (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تبحث هذه الدراسة في إمكانية تحديد العوامل الأساسية التي تساعد في التطبيق الناجح لبرامج تكلفة الجودة في الشركات الصناعية السورية من خلال تحديد مشاكل التطبيق, فاستندت على استكشاف ومسح لعينة من الشركات السورية بالاعتماد على قائمة استقصاء ومقابلات شخصية مع المدراء الأساسيين فيها لتحديد مدى وعي الإدارات لفوائد تطبيق هذا البرنامج من خلالها, وتوصلت الدراسة إلى أنه يوجد العديد من الأسباب التي تعرقل عملية التطبيق منها نقص ثقافة الجودة التي انعكست في عدم تقبل هذا البرنامج, البيئة التقليدية للأعمال, وهناك مجموعة من العوامل التي تساعد في تطبيق هذا البرنامج هي تبني ودعم الإدارة العليا, الثقافة التنظيمية للجودة المعتمدة على الدورات التدريبية, تبني التطبيقات الحديثة المؤتمتة. و توصي الباحثة بالإضافة إلى ضرورة تطبيق هذا البرنامج اعتماداً على العوامل المذكورة, التركيز في الدراسات اللاحقة على تحليل هذه العوامل ووضع الأساليب لضبط تكاليف الجودة السيئة من خلال إجراء الدراسات التجريبية لهذا البرنامج في الشركات المحلية ودراسة العوامل المؤثرة بتكاليف الفشل. This research studies the possibility of identification of the basic factors that help the successful implementation of Quality Costing Programs in Syrian Industrial Companies through identification of implementation problems. The study, which was based on a survey and investigation of a sample of Syrian Companies by using on a questionnaire and personal interviews with the principle directors, identified the extent of the establishment's awareness of the advantages of implementing this program. The study concluded that there are varieties of reasons that hinder the implementation process, such as: lack of quality education which was expressed by administrations disregard of this program, and the traditional environment of businesses. The basic factors that help in implementing this program is the support of the higher administration, the organizational of education quality based on the training courses, and adopting the automated modern applications (modern application software). The researcher recommends the implementation of this program based on the previous factors, an increase in the following study on the analysis of these factors, set methods to control the poor quality costs by empirical studies of this program in the local companies and study the effective factors of failure costs.